Free Flap Reconstruction of the Anterior Skull Base: A Systematic Review - Dang, Rajan P.; Ettyreddy, Abhinav R.; Rizvi, Zain; Doering, Michelle; Mazul, Angela L.; Zenga, Joseph; Jackson, Ryan S.; Pipkorn, Patrik (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Given the limitations in the available literature, the precise indications, techniques, and outcomes of anterior skull base free flap reconstruction remain uncertain. The objective of this study was to perform a systematic review of published literature and evaluate indications, methods, and complications for anterior skull base free flap reconstruction.Methods A systematic review of the literature was performed using a set of search criteria to identify patients who underwent free flap reconstruction of the anterior skull base. Articles were reviewed for inclusion based on relevance, with the primary outcome being surgical complications.Results After a comprehensive search, 406 articles were obtained and 16 articles were ultimately found to be relevant to this review—79 patients undergoing free flap reconstruction were identified. Overall complication rates were 17.7% (95% confidence interval [CI]: 16.6–33.1%) for major complications and 19.0% (95% CI: 17.8–35.5%) for minor complications.Conclusion Microvascular reconstruction of the anterior skull base is feasible with high reliability reported in the literature.
Keywords: systematic review; anterior; skull base; free flap; reconstruction